Iron‐Catalyzed Vinylic C−H Alkylation with Alkyl Peroxides. Issue 17 (4th July 2018) - Ge, Liang; Jian, Wujun; Zhou, Huan; Chen, Shaowei; Ye, Changqing; Yu, Fei; Qian, Bo; Li, Yajun; Bao, Hongli
Abstract: A variety of alkyl peresters and alkyl diacyl peroxides, which are readily accessible from carboxylic acids, are utilized as general primary, secondary, and tertiary alkylating reagents for iron‐catalyzed vinylic C−H alkylation of vinyl arenes, dienes, and 1, 3‐enynes. This transformation affords olefinic products in up to 98 % yield with high E / Z values. A broad range of functionalities, including carboxyl, boronic acid, methoxy, ester, amino, and halides, are tolerated. This protocol provides a facile approach to some olefins that are difficult to access, and hence, offers an alternative to existing systems. The synthetic utility of this method is demonstrated by late‐stage functionalization of selected natural‐product derivatives. Abstract : Iron‐clad alkylation : A variety of alkyl peresters and alkyl diacyl peroxides synthesized from carboxylic acids are utilized as general primary, secondary, and tertiary alkylating reagents for the iron‐catalyzed vinylic C−H alkylation of vinyl arenes, dienes, and 1, 3‐enynes (see scheme). Good functional group tolerance is observed and late‐stage functionalizations of selected natural product derivatives are demonstrated.